2023
DOI: 10.3390/ijms24076201
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor 1-Alpha and Glucose Metabolism during Cardiac Remodeling Progression from Hypertrophy to Heart Failure

Abstract: In pathological cardiac hypertrophy, the heart is more dependent on glucose than fatty acids. This shift in energy metabolism occurs due to several factors, including the oxygen deficit, which activates hypoxia-inducible factor-1α (HIF-1α), a critical molecule related to glucose metabolism. However, there are gaps regarding the behavior of key proteins in the glycolytic pathway and HIF-1α during the transition from hypertrophy to heart failure (HF). This study assesses the hypothesis that there is an early cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…A recent study conducted in our laboratory found a time‐dependent increase in HIF1‐α levels during the worsening of cardiac function. 47 These results strengthen the assumption that early exercise, by angiogenesis supporting, can mitigate the PO‐induced myocardial hypoxia, as the present data of normalized HIF1‐α expression points out.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study conducted in our laboratory found a time‐dependent increase in HIF1‐α levels during the worsening of cardiac function. 47 These results strengthen the assumption that early exercise, by angiogenesis supporting, can mitigate the PO‐induced myocardial hypoxia, as the present data of normalized HIF1‐α expression points out.…”
Section: Discussionsupporting
confidence: 87%
“…HIF-1α is a pivotal transcription factor activated in response to hypoxic conditions. It plays a crucial role in regulating the expression of a myriad of genes and actively participates in cellular stress responses [38]. In pathological states characterized by hypertension and obesity, the expression levels of HIF-1α in myocardial tissue macrophages are notably elevated.…”
Section: Discussionmentioning
confidence: 99%
“…These changes limit mitochondrial metabolism, resulting in a state of greatly reduced energy production instead of reduced oxygen consumption, which can reduce oxidative stress [ 91 ]. Recent in vivo studies in a rat model of aortic stenosis and chronic heart failure have suggested that HIF-1α is partly responsible for these metabolic alterations, although other underlying mechanisms may play a role as well [ 92 ]. Based on these considerations we hypothesize that the administration of HIF-PHIs to patients with heart failure is likely to further exacerbate the imbalance between ATP demand and supply.…”
Section: Suspected CV Abnormalities Linked To Hif-phismentioning
confidence: 99%